Un itinerario hacia la hospitalidad : reflexiones en torno a “El buen samaritano” de Vincent Van Gogh - Torres Brizuela, Ricardo (2019)
Fil: Torres Brizuela, Ricardo. Pontificia Universidad Católica Argentina; Argentina